Address by the President of the Institute and Faculty of Actuaries Dr David Hare. (9th July 2014) - Watts, D.
<x content-type="archive" xml:space="preserve">Abstract</x> In his Presidential Address, Dr Hare talks about the theme for his presidency, ensuring that the profession is relevant in the current environment. He outlines some of the recent changes in the economic environment and the financial services industry. He then sets out each element of the profession's strategy and discusses elements that he intends to champion during his Presidency to ensure that it remains relevant. He concludes by stating the profession's vision.